Communication Challengers Between Individuals: An Introduction to Social Psychology - Tirta Rhamadanty (ASTEEC, 2023)
This paper deals with the challenges of communication between individuals who are studied with social psychology glasses. The question that arises in this writing is how the challenge arises in communication between individuals and how understanding of social psychology helps overcome communication challenges. The writing uses a kind of qualitative approach using library research or literature study aimed at reviewing the challenges of communication between individuals across social psychology. As for the result of this writing, there are several challenges of communication between individuals, differing perceptions, nonverbal communication, the author of social norms, prejudices and stereotypes, disagreements and conflicts, and technological limitations. In the context of communication, an understanding of the principles of social psychology can help overcome obstacles and increase communication's effectiveness. Psychology social views that in overcoming the challenges of communicating between individuals, communicators need to communicate more effectively, avoid misunderstandings, and build stronger and healthier relationships with people in diverse social environments.